Importance of Anamnesis in Clinical Diagnosis of Cow Diseases - Tawfeeq, Mohammad Monir (Journal of Natural Sciences – Kabul University, 2021)
The diagnosis of animal diseases in veterinary clinics is often difficult and complex. Even though diagnostic methods in both human and veterinary medicine have significantly advanced, anamnesis retains its unique importance. Recording an animal's history and obtaining information from the owner are critical because animals cannot express their problems as humans do. Therefore, veterinarians must rely on specific methods to diagnose and treat animal diseases. History-taking involves recording information about the animal's food, water, environment, treatments, vaccinations, previous illnesses, and any abnormalities observed by the owner. This article reviews the importance of anamnesis in the clinical diagnosis of animal diseases.